PANCA JIWA AS SOCIAL CAPITAL APPROACH: AN ALTERNATIVE STARTEGY FOR ISLAMIC ECONOMIC DEVELOPMENT - Syamsuri Syamsuri (Share: Jurnal Ekonomi dan Keuangan Islam, 2019)
The economic issue is considered as a universal issue; one of the major problems in economy is the backwardness of economic development in rural areas. This study aims at seeking solutions using panca jiwa concepts of Pondok Gontor (sincerity, simplicity, self-sufficiency, Islamic brotherhood and freedom) as a social capital of the economic development in underdeveloped areas. This research employed a qualitative method as it is relevant in revealing details on the phenomenon. Data was gathered through interview, observation, and documentation. The collected data was then analyzed inductively and presented descriptively. The finding shows that the study area has a potent of panca jiwa, a potential to become an economic development strategy in solving poverty and underdevelopment which remained unsolved for decades.